2017
DOI: 10.1039/c7cy00890b
|View full text |Cite
|
Sign up to set email alerts
|

Ethane and ethylene aromatization on zinc-containing zeolites

Abstract: The importance of balance between the number of Zn and Brønsted acid sites for aromatization of ethane and ethylene on Zn-ZSM-5 is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 58 publications
3
67
0
Order By: Relevance
“…did not observe an activation period when feeding C 2 H 4 to Mo/HZSM‐5. Both ethylene as well as acetylene were shown to immediately oligomerize with near to 100 % conversion when contacted with a zeolite even at 300 °C, while ethane reacts more slowly . With both reactants, deactivation of the catalyst due to coking is fast .…”
Section: C2 Intermediatesmentioning
confidence: 99%
See 2 more Smart Citations
“…did not observe an activation period when feeding C 2 H 4 to Mo/HZSM‐5. Both ethylene as well as acetylene were shown to immediately oligomerize with near to 100 % conversion when contacted with a zeolite even at 300 °C, while ethane reacts more slowly . With both reactants, deactivation of the catalyst due to coking is fast .…”
Section: C2 Intermediatesmentioning
confidence: 99%
“…Both ethylene as well as acetylene were shown to immediately oligomerize with near to 100 % conversion when contacted with a zeolite even at 300 °C, while ethane reacts more slowly . With both reactants, deactivation of the catalyst due to coking is fast . Although most often ethylene, ethane and acetylene are proposed as reaction intermediates, higher intermediates are conceivable as well, especially if ethylene strongly adsorbs on the active metal and has to further react with gas‐phase CH 4 to desorb.…”
Section: C2 Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the low price of natural gas – and even declining over time ‐, natural gas opens up an opportunity to produce BTX from the light hydrocarbon components of natural gas. Considering that ethane is often an abundant component in natural gas, the process for the direct conversion of ethane to BTX has gained increased attention in the industry for the last few decades . Hence, this work is focused on studying the direct conversion of ethane into BTX.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the most effective catalyst is zinc containing ZSM‐5. Mehdad et al . investigated the conversion of ethane and ethylene on zinc‐containing SSZ‐13 and ZSM‐5.…”
Section: Introductionmentioning
confidence: 99%